Improvement of Agarwood Oil Extraction by Heat Transfer Control in Multiple Hydrodistillation Systems - S. A., Che Ghani; Mohd Nasri, Muda; Mueller, Timo Michael; W. S., Wan Harun; Saiful Nizam, Tajuddin; M., Ishak; Anwaruddin, Hisyam (Knowledge Transfer Programme, 2017)
Quantity of oil, and chemical composition of the Agarwood essential oil should be evaluated to determine the performance of an extraction system. The aim of this work was to investigate the effects of heat transfer control (HTC), applied at three hydrodistillation systems simultaneously, on the quantitative and qualitative characteristics of extracted essential oil from inoculated Agarwood, compared to a conventional hydrodistillation (HD). The extractions by conventional and HTC-ed HD procedures were done by supplying heat from liquefied petroleum gas (LPG); the ratio of the raw material to be extracted and the solvent was 0.1 g·mL-1 and the extraction time was 72 hours. The compositions of the extracted essential oils (using HTC-ed HD and conventional HD) were assessed using gas chromatography with flame ionization detector (GC–FID). The results of the extraction processes show that the extraction of inoculated Agarwood essential oil by HTC-ed HD is faster and produces higher yields compared to the extraction by conventional HD method. Further, the testing of the chemical properties of the Agarwood oil shows that essential oil obtained by HTC-ed HD has better quality compared to the oil obtained by conventional HD. The implementation of optimum thermal management in HTC-ed HD technology in Agarwood essential oil production industry is therefore of great importance.